Traumatismos de la mano: Round Table Hand traumatism XXVII Congreso Uruguayo de Cirugía; coordinator Enrique Pera Erro - Pera Erro, Enrique; Irigaray, Alberto; Sarlo, Mario; Inzaurralde, Oscar; Bonavita, Eugenio (Cirugía del Uruguay, 1978)
The topic was divided into 5 parts, by as many speakers, trying to group in each one of them, the most frequent injuries and their current treatment. It includes: anatomical overview soft tissue trauma extensor tendon and radial nerve injuries tendon and nerve injuries severe osteoarticular trauma